2016
DOI: 10.1016/j.rmed.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of adverse obstetrical and perinatal outcome in pregnancies complicated by asthma: A case control study

Abstract: The overall risk of adverse obstetrical and perinatal outcomes in pregnancies complicated by asthma is low compared to non-asthmatic women. Our observations suggest that enrollment into an asthma management program has a positive impact on overall pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 45 publications
0
42
0
2
Order By: Relevance
“…Even though all pregnant women referred to give birth at Hvidovre Hospital were informed and invited to this study, there could be a selection bias in women responding to the invitation. The women enrolled in the MAP cohort are comparable to the background population of pregnant women with regard to age and marital status . We have previously reported that the proportion of current smokers is lower in women participating in the MAP programmme than the background population of pregnant women .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Even though all pregnant women referred to give birth at Hvidovre Hospital were informed and invited to this study, there could be a selection bias in women responding to the invitation. The women enrolled in the MAP cohort are comparable to the background population of pregnant women with regard to age and marital status . We have previously reported that the proportion of current smokers is lower in women participating in the MAP programmme than the background population of pregnant women .…”
Section: Discussionmentioning
confidence: 93%
“…The women enrolled in the MAP cohort are comparable to the background population of pregnant women with regard to age and marital status . We have previously reported that the proportion of current smokers is lower in women participating in the MAP programmme than the background population of pregnant women . This uneven distribution could have influenced the results and affected the power to detect a difference regarding smoking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheduled follow-up visits were planned every 4 weeks during pregnancy with adjustment, if necessary, of asthma medication based on symptoms, level of fractional exhaled nitric oxide (F E NO), and spirometry in accordance with the algorithm subsequently described by Powell et al17 The MAP study has been described in detail previously 1821…”
Section: Methodsmentioning
confidence: 99%